WOMEN'S LEADERSHIP IN BUILDING MOTIVATION TO LEARN EARLY CHILDREN - Mabruroh, Mabruroh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Good school principal leadership can influence a pleasant and comfortable work atmosphere and optimally improve students' learning motivation. Involving female leaders, especially in the field of early childhood education, is very much needed with the nature of a woman who is gentle, patient, and full of compassion, making children more comfortable in building their talents. This study aimed to analyze and understand women's leadership in building children's learning motivation at KB Smart Ceria Pandean Paiton Probolinggo. This study uses a qualitative approach to the type of case study. The results showed that the first leader in KB Smart Ceria was a woman who had high enthusiasm in motivating teachers enthusiasm in implementing teaching and learning activities for students so that students were encouraged to increase their enthusiasm for learning. Second, the motivation carried out by the principal towards teachers in expanding the enthusiasm for learning in students is carried out by implementing a motivational program by becoming an educator, supervisor, innovator and motivator. With the implementation of management motivation by the principal at the Smart Ceria KB, the enthusiasm for learning of students is more active and exploratory, and the level of effort in learning indicators is increasing.